2016
DOI: 10.1073/pnas.1600476113
|View full text |Cite
|
Sign up to set email alerts
|

Apicomplexa -specific tRip facilitates import of exogenous tRNAs into malaria parasites

Abstract: The malaria-causing Plasmodium parasites are transmitted to vertebrates by mosquitoes. To support their growth and replication, these intracellular parasites, which belong to the phylum Apicomplexa, have developed mechanisms to exploit their hosts. These mechanisms include expropriation of small metabolites from infected host cells, such as purine nucleotides and amino acids. Heretofore, no evidence suggested that transfer RNAs (tRNAs) could also be exploited. We identified an unusual gene in Apicomplexa with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…These data directly support our previous proteomic labeling experiments performed with P. falciparum salivary gland sporozoites that robustly showed that PfPABP1 is surface exposed ( 33 ). Moreover, this is the third RNA-binding protein known to localize on the surface of sporozoites, as tRip and GAPDH were also recently found to localize on the surface as well ( 34 , 41 ). Taking the results together, we found that PyPABP1 is localized in the cytosol and nuclear periphery throughout the sexual and asexual blood stages but becomes surface localized and is shed by salivary gland sporozoites during gliding motility.…”
Section: Resultsmentioning
confidence: 98%
“…These data directly support our previous proteomic labeling experiments performed with P. falciparum salivary gland sporozoites that robustly showed that PfPABP1 is surface exposed ( 33 ). Moreover, this is the third RNA-binding protein known to localize on the surface of sporozoites, as tRip and GAPDH were also recently found to localize on the surface as well ( 34 , 41 ). Taking the results together, we found that PyPABP1 is localized in the cytosol and nuclear periphery throughout the sexual and asexual blood stages but becomes surface localized and is shed by salivary gland sporozoites during gliding motility.…”
Section: Resultsmentioning
confidence: 98%
“…However, new functions have arisen in unicellular eukaryotes. For example, in Plasmodium , the GST fusion in tRip is localized in the parasite membrane and is involved in tRNA trafficking . The Yip1‐OB fusion present in P .…”
Section: Discussionmentioning
confidence: 99%
“…However, new functions have arisen in unicellular eukaryotes. For example, in Plasmodium, the GST fusion in tRip is localized in the parasite membrane and is involved in tRNA trafficking [37]. The Yip1-OB fusion present in P. aphanidermatum is another example of a possible membrane protein with an OB-fold tRNA-binding domain, of unknown function in this case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unicellular protozoans encode near the theoretical minimum of tRNA genes, such as the malaria parasite Plasmodium falciparum, which has only 35 tRNA genes (43). P. falciparum was recently found to import additional tRNAs from its host (44). Some species of fish have astoundingly high tRNA gene numbers (Table S2), such as the elephant shark (Callorhinchus milii), which encodes 13,724 tRNAs (43).…”
Section: Trna Function and Regulationmentioning
confidence: 99%